(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2015)
The 3D structure of the insecticidal protein Cry1Ba4 produced by B. thuringiensis subsp. Entomocidus HD-9 was determined using homology modelling. From the model built, we have been able to identify the possible sites for structure modification by site-directed mutagenesis. The mutation was introduced at the conserved region of Î±-helix 7 by substituting the hydrophobic motif that comprises alanine 216, leucine 217 and phenylalanine 218 with arginine. Wild and mutant Cry1Ba4 genes were cloned into pET200/D-TOPO and expressed in the expression host. The result suggests that mutant Cry1Ba4 protein was less toxic to the larvae Plutella xylostella compared to the wild-type. In conclusion, alteration in the structure of Domain I had left an impact on the toxicity of Cry1Ba4 against P. xylostella.